1990
DOI: 10.1111/j.1651-2227.1990.tb11522.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of Low Doses of Recombinant Yeast‐Derived Hepatitis B Vaccine

Abstract: The immunogenicity and safety of recombinant yeast-derived hepatitis B vaccine given in doses of 0.6 microgram, 1.25 microgram, 2.5 micrograms and 5.0 micrograms were studied in 4 comparable groups of children aged 1-12 years. All children received three doses of vaccine at time 0, 1 month and 5 months. Immunogenicity appeared to be satisfactory in all 4 groups of children. In the early phase of the study, a dose-response relationship was observed but there was no significant difference in the geometric mean t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Oon et al showed a reduction in transmission rates by as much as 85% with 5 µg and 10 µg doses of vaccine. 16 Tan et al 17 also showed that very low dose vaccine (as low as 0.6 µg) was also able to produce lasting protective antibody response, even up to 48 months as documented by Goh et al 18 In Singapore therefore based on these studies, the practice, with the H-B-Vax vaccine (used in this study), has been to administer 2.5 µg of vaccine for those with maternal hepatitis B-negative status and 5.0 µg for those with positive maternal hepatitis B status. Since the implementation of hepatitis B vaccination programme, the vaccine uptake rate has been satisfactory, with vaccination achieved in approximately 90% of newborns, as reviewed in 1991 by Quak.…”
Section: Discussionmentioning
confidence: 99%
“…Oon et al showed a reduction in transmission rates by as much as 85% with 5 µg and 10 µg doses of vaccine. 16 Tan et al 17 also showed that very low dose vaccine (as low as 0.6 µg) was also able to produce lasting protective antibody response, even up to 48 months as documented by Goh et al 18 In Singapore therefore based on these studies, the practice, with the H-B-Vax vaccine (used in this study), has been to administer 2.5 µg of vaccine for those with maternal hepatitis B-negative status and 5.0 µg for those with positive maternal hepatitis B status. Since the implementation of hepatitis B vaccination programme, the vaccine uptake rate has been satisfactory, with vaccination achieved in approximately 90% of newborns, as reviewed in 1991 by Quak.…”
Section: Discussionmentioning
confidence: 99%
“…Effectiveness of HBV vaccination was estimated from randomized and nonrandomized studies of recombinant HBV vaccines. [87][88][89][90][91][92] In the perinatal stage, a complete series of HBV immunization and a single dose of HBV immune globulin at birth resulted in 92% to 98% protection from vertical HBV transmission. In the horizontal stage, we assumed that, on the basis of long-term pediatric follow-up and clinical trials in adolescents and adults, [93][94][95] protection from HBV infection was nearly equivalent to protection achieved from vaccination at birth.…”
Section: Hepatitis B Virusmentioning
confidence: 99%